Asymmetric Wholesale Pricing: Theory and Evidence - Sourav Ray; Haipeng (Allan) Chen; Mark Bergen; Daniel Levy (Bar-Ilan University, Department of Economics, 2005)
Asymmetric pricing is the phenomenon where prices rise more readily than they fall. We articulate, and provide empirical support for, a theory of asymmetric pricing in wholesale prices. In particular, we show how wholesale prices may be asymmetric in the small but symmetric in the large, when retailers face costs of price adjustments. Such retailers will not adjust prices for small changes in their costs. Upstream manufacturers then see a region of inelastic demand where small wholesale price changes do not translate into commensurate retail price changes. The implication is asymmetric – small wholesale increases are more profitable because manufacturers will not lose customers from higher retail prices; yet, small wholesale decreases are less profitable, because these will not create lower retail prices, hence no extra revenue from greater sales. For larger changes, this asymmetry at wholesale vanishes as the costs of changing prices are compensated by increases in retailers' revenue that result from correspondingly large retail price changes. We first present a formal economic model of a channel with forward looking retailers facing costs of price adjustment to derive the testable propositions. Next, we test these on manufacturer prices in a supermarket scanner dataset to find support for our theory. We discuss the contributions of the results for the asymmetric pricing, distribution channels and cost of price adjustment literatures, and implications for public policy.
Keywords: E31; E12; L11; L16; L22; L81; M21; M31; 330; Asymmetric Pricing; Channel Pricing; Costs of Price Adjustment; Menu Costs; Wholesale Prices; Channels of Distribution; Retailing; Scanner Data